The Heterogeneous Effect of Information on Student Performance : Evidence from a Randomized Control Trial in Mexico - Avitabile, Ciro; de Hoyos, Rafael (World Bank, Washington, DC, 2015)
A randomized control trial was conducted to study whether providing 10th grade students with information about the returns to upper secondary and tertiary education, and a source of financial aid for tertiary education, can contribute to improve student performance. The study finds that the intervention had no effects on the probability of taking a 12th grade national standardized exam three years after, a proxy for on-time high school completion, but a positive and significant impact on learning outcomes and self-reported measures of effort. The effects are larger for girls and students from households with a relatively high income. These findings are consistent with a simple model where time discount determines the increase in effort and only students with adequate initial conditions are able to translate increased effort into better outcomes.